Investigation of antioxidant properties of metal ascorbates and their mixtures by voltammetry; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Vtorushina A. N. Anna Nikolaevna (2015, 2015)
Title screen